Commercial companies in the Islamic Maghreb "credit and agency" as a model. (6-8AH/12-14AD) - حمود علا; شيرين حمودي; وفاء صارم (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The history of the economic aspect is a necessity to form an integrated historical picture of the Islamic Maghreb, because the economic factor has strong repercussions on society and the behavior of its members. The researcher of the history of Morocco notes that the Moroccan economy has mainly been based on trade, and commercial dealings often took the form of “companies” that reached a remarkable degree of diversity. They are the two companies ; credit and agency, by referring to the appropriate historical sources, to clarify the meaning of the company, with a mention of the conditions for writing its contracts in a correct manner, in addition to addressing the disputes that arose around it and the obligations to resolve and cancel it, in order to form a clear picture of one of the most prominent commercial systems prevailing at the time.